Chaos Theory and Example of Use in Nursing: Bypass Surgery - Menevşe Samur; Şeyda Seren İntepeler (Association of Nurse Managers, 2017)
The chaos theory is trying to explain nature events with physics, chemistry and mathematic tests and firstly emerged in the nature sciences. Health care systems are complex in terms of patients, workers, illnesses, work environments and requires high technologies and this creates the theory an application area. Chaos theory is used to root causes for change, especially in explaining the behavior of complex systems. Chaos theory can be used in the planning of nursing practice because it contains complex and dynamic processes. This article aims to explain the chaos theory by questioning the usability, to discuss and facilitate understanding of theory via an example.